Liposomal amphotericin B—the present. (25th November 2022) - Maertens, J; Pagano, L; Azoulay, E; Warris, A
Abstract: Most invasive fungal infections are opportunistic in nature but the epidemiology is constantly changing, with new risk groups being identified. Neutropenia is a classical risk factor for fungal infections, while critically ill patients in the ICU are now increasingly at risk of yeast and mould infections. Factors to be considered when choosing antifungal treatment include the emergence of rarer fungal pathogens, the risk of resistance to azoles and echinocandins and the possibility of drug–drug interactions. Liposomal amphotericin B has retained its place in the therapeutic armamentarium based on its clinical profile: a broad spectrum of antifungal activity with a low risk of resistance, predictable pharmacokinetics with a rapid accumulation at the infection site (including biofilms), a low potential for drug–drug interactions and a low risk of acute and chronic treatment-limiting toxicities versus other formulations of amphotericin B. It is a suitable choice for the first-line empirical or pre-emptive treatment of suspected fungal infections in neutropenic haematology patients and is an excellent alternative for patients with documented fungal disease who can no longer tolerate or continue their first-line azole or echinocandin therapy, both in the haematology setting and in the ICU. Moreover, it is the first-line drug of choice for the treatment of invasive mucormycosis. Finally, liposomal amphotericin B is one of the few antifungal agents approved for use in children of all ages over 1 month and is included in paediatric-specific guidelines for the management of fungal disease.